STRESS FACTORS OF LABOR CONSTRUCTION OF BUILDING CONSTRUCTION ON PERFORMANCE TIME AND COST - Robin Supratman; Dwi Dinariana; Hari Nugraha Nurjaman; Arman Jayady; Fitri Suryani (International Journal Labs, 2022)
Human resources are an important factor in the implementation of construction projects. This is because the role of human resources is very dominant where HR is the main driving force in construction project work, so the quality of human resources is a determining factor for the success of a project. The purpose of this study is to make a regression model equation that can be used to predict the stress factor of construction workers (consultants and contractors) of buildings on time and cost performance. This research method uses a survey, namely by distributing questionnaires to collect main data to obtain facts by taking samples from the population. The results showed that the stress factors for building construction workers (contractors) that affect time performance were that I was not confident with my work because I did not complete the task properly (X18) and there were no definite regulations from the company regarding the workforce career development process. work (X22).